Identification of 1,3-1,4-β-D-glucanase (OsDLH) genes and analysis of haplotype diversity in rice - Zhu, Manqiong; Zhou, You; Zhang, Meng; Bao, Yaling; Wang, Chunni; Lv, Wenhao; Tang, Chenghang; Zhu, Jun; Tao, Kailiang; Chen, Ruofan; Zhang, Jinguo; Arabboevich, Ergashev Mukhammadjon; et al. (Frontiers in Plant Science, 2025)
1,3-1,4-β-D-glucanase (DLH) is a fibrolytic enzyme playing important roles in plant growth, development, and stress response. In this study, we identified 11 DLH genes in japonica rice (Nipponbare), and analyzed their chromosomal localization, physicochemical properties, subcellular localization, evolutionary relationships, and collinearity. We also performed cis-acting element identification, gene expression profiling, and qPCR verification under abiotic stress, as well as conducted diversity analysis of gene-CDS-haplotypes (gcHaps) in 3,010 rice germplasms to dissect the potential functions of these OsDLH genes. The results showed that OsDLH1, OsDLH5, and OsDLH10 can be utilized to improve the tolerance of rice to abiotic stress. OsDLH1, OsDLH2 and OsDLH8 are highly expressed in roots. Under high-salt stress, the expression of OsDLH6 and OsDLH10 in stems and leaves increased. These results indicated that OsDLH1 and OsDLH5 have specific expression patterns in response to different environmental signals, implying that they may play different roles in the growth and development process of rice and the stress response mechanism. Haplotype analysis indicated population differentiation of the OsDLH gene family in rice. The major gcHaps at most OsDLH loci are significantly associated with yield traits. Some genes of this family have potential application value in improving stress resistance and yield traits of rice.